Pendekatan Capacity Building dalam Peningkatan Kapasitas Manajerial Pengelola Klub Sepak Bola Amatir di Surabaya - Gandi Aswaja Yogatama; Muhammad Tahajjudi Ghifary; Ardyan Wicaksana; Dyajeng Puteri Woro Subagio; Prasetyo Alif Soeprawiro; Allen Pranata Putra (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
The rapid growth of amateur football clubs in Surabaya presents great opportunities for talent development and social cohesion, but it also comes with managerial challenges such as unclear organizational structure, lack of financial transparency, limited promotion, and the absence of operational standards for matches. This article presents the results of a community service program based on capacity building, designed to strengthen the managerial capacity of amateur football club managers in Surabaya. The activities focused on a one-day face-to-face workshop for representatives from 30 clubs, utilizing interactive lectures, local case studies, targeted discussions, and the distribution of practical handouts including organizational structure templates, code of conduct, one-page financial reports, content calendars, and matchday checklists. The core materials covered five areas: governance & legal, planning & OKR, finance & accountability, marketing & sponsorship, and operations & safeguarding. The program concludes that a brief, capacity-building workshop can trigger the initial professionalization of amateur football clubs through measurable, easy-to-adopt, and replicable minimum viable governance practices. These findings are relevant as a model for strengthening governance and management of amateur clubs in Indonesia, while also supporting a more professional, accountable, and sustainable community sports ecosystem.